Optimalisasi Laporan Keuangan Berbasis Pivotable pada Badan Usaha Milik Desa : (Aplikasi pada BUMDes Bahtera, Desa Mertoyudan, Kecamatan Mertoyudan, Kabupaten Magelang) - Veni Soraya Dewi; Azmia Salsabilla; Anggun Dwi Cahyani; Tifa Anggun Hapsari; Amalia Susanti (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2023)
This Thematic Real Work Lecture aims to improve the financial performance of BUMDes through the preparation of financial reports with Pivotables. This activity was carried out at BUMDes Bahtera located on Jalan Sudiro, Mertoyudan, Magelang. Problems that arise include limited human resources, the preparation of BUMDes financial reports is still done manually, the cost of goods sold calculation system is not in accordance with SAK, the business subunits owned by BUMDes are still limited. In order to overcome these problems, the Thematic KKN team conducted socialization, training, and assistance in making financial reports using pivotables to BUMDes management, especially treasurers and sales staff. The results achieved in this Thematic KKN activity are the increased knowledge and skills of BUMDes Bahtera management regarding the preparation of pivotable-based financial reports. From the results of these activities, it is expected that the preparation of pivotable financial reports will be carried out consistently so that it will improve the quality of financial reports.